Presence pedagogy: a necessary practice in school (Research, Society and Development, 2022)
This article is part of the scope of the master's research, in progress and aims to understand good practices and references on the success of Pedagogy of Presence in the teaching-learning process in a full-time school, also known as full school, located in the municipality of Várzea Grande/MT. This is a case study qualitative research and the data were obtained through an interview with teachers and students of the aforementioned school. For data analysis, categories were constructed in the light of Bardin and the theoretical contribution will be based mainly on Freire, Costa and Almeida, who discuss human relationships, based on affective education and reflective educational practices. In a preliminary analysis, it is possible to conclude that both teachers and students understand the correlation between affection and learning by applying the Pedagogy of Presence as constructive and positive and its influence to the teaching-learning process.